Occurrence of the psyllid Trioza tabebuiae Burckhardt & Santana, 2001 (Hemiptera: Triozidae) in Argentina, a potential pest of the Pink Trumpet tree Handroanthus heptaphyllus (Vell.) Mattos, 1970 (Lamiales: Bignoniaceae) - Baliotte, Carla; Dellapé, Gimena; Bouvet, Juan P.; Aquino, Daniel A. (Entomological Communications, 2023)
Trioza tabebuiae Burckhardt & Santana, 2001 is an important pest of some ornamental plants species of the family Bignonaceae in Brazil. This psyllid causes serious damages in leaves of Handroanthus Mattos, 1970 tress curving its margins which reduce the photosynthetic area when high infestations. In Argentina, Handroanthus heptaphyllus (Vell.) Mattos, 1970 is a relevant tree for its wood and for ornamental use. Here, we report for the first time the presence of the psyllid T. tabebuiae associated with the bignonaceous tree H. heptaphyllus in Argentina. Moreover, the damage produced by T. tabebuiae in leaves of the Pink Trumpet trees was observed.